2016
DOI: 10.4238/gmr.15017130
|View full text |Cite
|
Sign up to set email alerts
|

BMP6 and BMP4 expression in patients with cancer-related anemia and its relationship with hepcidin and s-HJV

Abstract: ABSTRACT. In the present study, we investigated BMP6 and BMP4 expression in patients with cancer-related anemia (CRA) as well as its relationship with hepcidin and s-HJV. The avidin-biotin system enzymelinked immunosorbent assay was used to test serum levels of BMP6, BMP4, s-HJV, and hepcidin in 53 cancer patients with anemia and 52 control cancer patients without anemia. Serum levels of BMP6 and hepcidin in the anemia group were 434.53 ± 212.11 ng/mL and 5.68 ± 3.89 µg/L, respectively. In the non-anemia cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Elevated expression of Hepcidin can inhibit the intestinal iron absorption and inhibit the release of iron from the mononuclear macrophage system, which makes the iron storage in the cells, iron reduction in bone marrow, and ultimately lead to iron loss and anemia [18,20-22]. Our previous studies [19] also showed that Hepcidin plays an important role in the treatment of postoperative radiotherapy and chemotherapy in patients with advanced tumor anemia, the expression of hepcidin in patients with anemia was significantly higher compared with that of patients without anemia (P<0.05), which was negatively correlated with Hb (r =-0.2597,P<0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated expression of Hepcidin can inhibit the intestinal iron absorption and inhibit the release of iron from the mononuclear macrophage system, which makes the iron storage in the cells, iron reduction in bone marrow, and ultimately lead to iron loss and anemia [18,20-22]. Our previous studies [19] also showed that Hepcidin plays an important role in the treatment of postoperative radiotherapy and chemotherapy in patients with advanced tumor anemia, the expression of hepcidin in patients with anemia was significantly higher compared with that of patients without anemia (P<0.05), which was negatively correlated with Hb (r =-0.2597,P<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is one of the common symptoms in patients with intestinal tumor. It is generally considered that the anemia is a chronic disease in chronic inflammation and malignant tumors (ACD), Current research [ 17 - 19 ] has confirmed that Hepcidin plays a key role in the occurrence and development of ACD [ 17 ]. Elevated expression of Hepcidin can inhibit the intestinal iron absorption and inhibit the release of iron from the mononuclear macrophage system, which makes the iron storage in the cells, iron reduction in bone marrow, and ultimately lead to iron loss and anemia [ 18 , 20 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both BMP9 and BMP10 have relatively high circulating levels in blood (~ 0.5-15 ng/mL) in both humans and mice [24,28,[41][42][43][44][45], indicating that they are delivered to endothelial cells via the bloodstream. BMP2, BMP4, and BMP6 serum levels are much lower (pg/ mL-low ng/mL range) [43,46,47] and are expressed in a temporally and spatially regulated manner developmentally [32,48], indicating paracrine interactions that affect endothelial cell behaviors. Interestingly, BMP2 and BMP4 mRNA and protein are also expressed in endothelial cells, suggesting autocrine or paracrine vascular effects that have not been well-explored [49][50][51][52][53][54][55].…”
Section: Bmp Ligands Involved In Endothelial Cell Functionmentioning
confidence: 99%
“…BMP-6 is secreted by endothelial cells in the liver to inform adjacent hepatocytes about elevated serum iron levels and replenished iron stores (110). Accordingly, BMP-6 is a major inducer of HAMP transcription and a potential mediator of CIA (111)(112)(113). Given the key role of BMP-6 for the induction of hepcidin, it is not surprising that neutralizing antibodies have been used to block hepcidin induction in preclinical and clinical models of ACD (114)(115)(116).…”
Section: Blocking Il-6 or Bmp-6 To Inhibit Hepcidin In Ciamentioning
confidence: 99%
“…BMP-6 and hepcidin levels are elevated in CIA which may aid in the diagnosis ( 112 , 113 ). Yet it remains unclear whether serum concentrations of these mediators predict the response to currently available treatments such as ESA and to therapies specifically targeting them ( 172 ).…”
Section: Diagnosis Of Ciamentioning
confidence: 99%